Penerapan Model Problem Based Learning Melalui Media Bamboozle untuk Meningkatkan Kosa Kata Bahasa Inggris Sekolah Dasar - Habsah, Ilvia; Habiby, M. Nuril Anwar; Putri, Linda Indiyarti (Jurnal Studi Multidisiplin Qomaruna, 2025)
Language is an important role in human life because language is a tool to convey information, intentions and goals. English is one of the subjects that plays a vital role in developing students’ language skills, including at the elementary school level. However, in practice, many elementary students still struggle with mastering English vocabulary due to limited teaching methods and low learning motivation. This study aims to improve students’ English vocabulary mastery through the application of a Problem-Based Learning (PBL) model supported by Baamboozle media. The research employed a Classroom Action Research (CAR) approach, conducted in two cycles consisting of planning, action, observation, and reflection stages. The participants were 35 fifth-grade students at UPT SD Negeri 287 Gresik. Data were collected through observations and vocabulary tests.The results indicate that the use of Baamboozle media increased students’ engagement, curiosity, and critical thinking in learning English vocabulary in a more enjoyable and meaningful way. The pre-test results showed that only 31% (11 students) met the Minimum Completeness Criteria (KKM), with an average score of 71.60%. After the intervention, vocabulary mastery improved: in Cycle I, 76.70% of students reached the “Sufficient” category (21 students), and in Cycle II, 85% achieved the “Good” category (28 students). These findings demonstrate that implementing the PBL model combined with interactive digital media can effectively enhance English vocabulary learning at the elementary level.